ANALYSIS OF THE ADVANTAGES AND DISADVANTAGES OF 2D MODELS\MOCKUPS IN LEARNING MEDIA - nesti evriyanti (Teaching and General Education Studies, 2026)
Learning media plays an important role in helping students understand the material more easily. One of the media frequently used in learning activities is a two-dimensional (2D) model or mockup. A 2D model/mockup is a visual medium that displays objects in the form of flat images, helping students understand concepts more clearly. This article aims to explain the meaning of 2D models/mockups in learning media and analyze their advantages and disadvantages in the learning process. The method used in writing this article is a literature study by reviewing various book and journal sources related to learning media. The results of the study indicate that 2D models/mockups have several advantages, such as being easy to make, relatively inexpensive, and able to help students understand the material visually and increase learning interest. However, 2D models/mockups also have several disadvantages, namely they cannot display objects realistically like three-dimensional media, the information conveyed is limited, and they are less interactive compared to digital-based learning media. Therefore, the use of 2D models/mockups should be combined with other learning media to make the learning process more effective and interesting for students.